A 3D‐Printed Self‐Adhesive Bandage with Drug Release for Peripheral Nerve Repair. Issue 23 (19th October 2020) - Zhang, Jiumeng; Chen, Yuwen; Huang, Yulan; Wu, Wenbi; Deng, Xianming; Liu, Haofan; Li, Rong; Tao, Jie; Li, Xiang; Liu, Xuesong; Gou, Maling
Abstract: Peripheral nerve injury is a common disease that often causes disability and challenges surgeons. Drug‐releasable biomaterials provide a reliable tool to regulate the nerve healing‐associated microenvironment for nerve repair. Here, a self‐adhesive bandage is designed that can form a wrap surrounding the injured nerve to promote nerve regeneration and recovery. Via a 3D printing technique, the bandage is prepared with a special structure and made up of two different hydrogel layers that can adhere to each other by a click reaction. The nanodrug is encapsulated in one layer with a grating structure. Wrapping the injured nerve, the grating layer of the bandage is closed to the injured site. The drug can be mainly released to the inner area of the wrap to promote the nerve repair by improving the proliferation and migration of Schwann cells. In this study, the bandage is used to assist the neurorrhaphy for the treatment of complete sciatic nerve transection without obvious defect in rats. Results indicate that the self‐adhesive capacity can simplify the installation process and the drug‐loaded bandage can promote the repairing of injured nerves. The demonstrated 3D‐printed self‐adhesive bandage has potential application in assisting the neurorrhaphy for nerve repair. Abstract : A self‐adhesive bandage consists of two layers made of two clickable materials. This bandage can adhere itself via a click reaction. Due to big specific surface area of the grating layer and blocking by the outer layer, drug is mainly distributed at the injured site to promote nerve repair and the side effects would be reduced.